A Proteomic Investigation of Hepatic Resistance to Ascaris in a Murine Model. - Gwendoline Deslyper; Thomas J Colgan; Andrew J R Cooper; Celia V Holland; James C Carolan (Public Library of Science (PLoS), 2016)
The helminth Ascaris causes ascariasis in both humans and pigs. Humans, especially children, experience significant morbidity including respiratory complications, growth deficits and intestinal obstruction. Given that 800 million people worldwide are infected by Ascaris, this represents a significant global public health concern. The severity of the symptoms and associated morbidity are related to the parasite burden and not all hosts are infected equally. While the pathology of the disease has been extensively examined, our understanding of the molecular mechanisms underlying resistance and susceptibility to this nematode infection is poor. In order to investigate host differences associated with heavy and light parasite burden, an experimental murine model was developed utilising Ascaris-susceptible and -resistant mice strains, C57BL/6J and CBA/Ca, respectively, which experience differential burdens of migratory Ascaris larvae in the host lungs. Previous studies identified the liver as the site where this difference in susceptibility occurs. Using a label free quantitative proteomic approach, we analysed the hepatic proteomes of day four post infection C57BL/6J and CBA/Ca mice with and without Ascaris infection to identify proteins changes potentially linked to both resistance and susceptibility amongst the two strains, respectively. Over 3000 proteins were identified in total and clear intrinsic differences were elucidated between the two strains. These included a higher abundance of mitochondrial proteins, particularly those associated with the oxidative phosphorylation pathway and reactive oxygen species (ROS) production in the relatively resistant CBA/Ca mice. We hypothesise that the increased ROS levels associated with higher levels of mitochondrial activity results in a highly oxidative cellular environment that has a dramatic effect on the nematode's ability to successfully sustain a parasitic association with its resistant host. Under infection, both strains had increased abundances in proteins associated with the oxidative phosphorylation pathway, as well as the tricarboxylic acid cycle, with respect to their controls, indicating a general stress response to Ascaris infection. Despite the early stage of infection, some immune-associated proteins were identified to be differentially abundant, providing a novel insight into the host response to Ascaris. In general, the susceptible C57BL/6J mice displayed higher abundances in immune-associated proteins, most likely signifying a more active nematode cohort with respect to their CBA/Ca counterparts. The complement component C8a and S100 proteins, S100a8 and S100a9, were highly differentially abundant in both infected strains, signifying a potential innate immune response and the importance of the complement pathway in defence against macroparasite infection. In addition, the signatures of an early adaptive immune response were observed through the presence of proteins, such as plastin-2 and dipeptidyl peptidase 1. A marked decrease in proteins associated with translation was also observed in both C57BL/6J and CBA/Ca mice under infection, indicative of either a general response to Ascaris or a modulatory effect by the nematode itself. Our research provides novel insights into the in vivo host-Ascaris relationship on the molecular level and provides new research perspectives in the development of Ascaris control and treatment strategies.